O Plano de Ações Articuladas - PAR: o processo de indução das políticas educacionais dos sistemas municipais de ensino - Oliveira, Beatriz Alves de (Universidade Federal de São Carlos, 2016)
The present research aims to analyze the complexity of the development, implementation and correlation between education public policies and educational management. The object of this research is the o Programa de Ações Articuladas (PAR) linked to other educational public policies such as: the O Programa de Desenvolvimento da Educação (PDE), Compromisso Todos pela Educação e o Índice de Desenvolvimento da Educação Brasileira (IDEB) .The interest in researching this topic is related to the importance of investigating the rationalization and the internationalization of educational public policies undertaken by the Brazilian State. The topic presents the following research questions: To what extent do the education public policies, planned by State, present homogeneous, regulatory and disciplinary characteristics? Do the public policies democratically meet or not the local interests and specificities? The aim of this study is to verify if the induction process of education policies connected to PAR has resulted in control and disciplinary policies of the educational action of municipalities by means of an internationalization policy of the Federal Government in the municipality spheres to improve the control of State or if the concretization of the PAR has been directed to the regional and local specificities. The methodological procedure is based on the bibliographical and documentary research and the data was collected through an online questionnaire. The theoretical framework of this investigation was based on the following categories: federalism, centralism/decentralism process, collaboration regime, autonomy, republican policy, social democracy policy, accountability, governance and soft power. Thereby, the PAR, like others Federal Government policies, has been implemented and used to consolidate measuring instruments and monitoring policies, thus introducing in the public education the governance forms to increasingly reduce the autonomy and capacity of local decision.
The Plano de Ações Articuladas - PAR: the process for inducing educational policies for municipal education systems
Keywords: Plano de Ações Articuladas; Federalismo; Regime de colaboração; Processo de centralização/descentralização; Accountability; Governança; Soft power; Federalism; Collaboration regime; Centralization/decentralization process; Governance; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL